MEASURING CO2 CONCENTRATION IN AIR (International Journal of Food and Nutritional Sciences, 2021)
The earth’s Atmospheric CO2 level is increasing day by day. The global average atmospheric carbon dioxide in 2019 was 409.8 parts per million and in October- 2020 it is 411.29. Carbon dioxide is a key greenhouse gas and responsible for about three-quarters of emissions. So co2 level monitoring has also started to gain importance.In our previous project, we used the Gravity Infrared CO2 sensor to measure the CO2 concentration in air. In this project, we are going to use an MQ-135 sensor with Arduino to measure the CO2 concentration. The measured CO2 concentration values will be displayed on the OLED module and last we will also compare the Arduino MQ-135 sensor readings with Infrared CO2 sensor readings. Apart from CO2, we have also measured the concentration of LPG, Smoke, and Ammonia gas using Arduino. For this project, we are using a Monochrome 7- pin SSD1306 0.96” OLED display. It can work on three different communications Protocols: SPI 3 Wire mode, SPI four-wire mode and I2C mode.